Strength, durability, thermal performance and sustainability assessment of one-part geopolymer concrete masonry units. - Bhayat, Moegamat Tashriq (Stellenbosch : Stellenbosch University, 2025)
Thesis (MEng)--Stellenbosch University, 2024.